2019
DOI: 10.21873/invivo.11556
|View full text |Cite
|
Sign up to set email alerts
|

Early Second Round Targeted Biopsy of PI-RADS Score 3 or 4 in 256 Men With Persistent Suspicion of Prostate Cancer

Abstract: Background/Aim: The aim of the study was to determine the rate of clinically significant prostate cancer (csPCa) cases in men submitted to early second round mpMRI/TRUS (multiparametric magnetic resonance imaging/transrectal ultrasound) fusion biopsy (TPBx).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The detection rates for overall PC were 80% (4/5), 53% (10/19), and 86% (6/7), respectively. In a study by Pepe et al [38], 256 patients with PI-RADS 3/4 lesions on mpMRI underwent early repeat prostate biopsy 6-9 months after an initial negative MRI/TRUS-guided fusion biopsy. The PC detection rate in repeat TB was 14% (36/256) and the sPC detection rate was 10% (26/256).…”
Section: Discussionmentioning
confidence: 99%
“…The detection rates for overall PC were 80% (4/5), 53% (10/19), and 86% (6/7), respectively. In a study by Pepe et al [38], 256 patients with PI-RADS 3/4 lesions on mpMRI underwent early repeat prostate biopsy 6-9 months after an initial negative MRI/TRUS-guided fusion biopsy. The PC detection rate in repeat TB was 14% (36/256) and the sPC detection rate was 10% (26/256).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is in this group where legitimate concern exists for false negative biopsies. Several retrospective studies recommend early re-imaging following a negative mpMRI guided biopsy of PI-RADS 4 or 5 ROI providing the repeat mpMRI remains suspicious for csPCa [ 6 , 7 ]. Our observation that ipsilateral SB increases detection of csPCa missed by MR targeted biopsy suggests the real potential for false negative MRFTB due to mis-registration [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we routinely recommend initial biopsy for all PI-RADS 3-5 ROI. There is increasing evidence that MRI-targeted biopsy alone fails to detect csPCA in some PI-RADS 4 and 5 ROI [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Well, should the second round of fusion biopsy be performed on patients whose FPB histopathology is benign, but cancer continues to suspicious? Pepe et al reported that in patients with a negative FPB (transperineal saturation plus TB) history and PIRADS-3 lesion, approximately 2.5% cancer was detected with the second round of TB 17. In the future, we believe that with the increasing experience of fusion biopsy, clinicians performing PB will make a lot of effort to answer this question.Shakir et al evaluated CDR and histological PCa upgrading with targeted biopsy according to different PSA levels and reported that the PSA cutoff for histological PCa upgrading was 5.2 ng/mL.…”
mentioning
confidence: 94%